Expression Profile of Luteinizing Hormone Receptor Gene in Hierarchal Follicles and Regressing Oviduct Tissues of White Leghorn Hens During Moulting. Issue 2 (16th July 2012) - Agarwal, R; Sastry, KVH; Tripathi, V; Singh, R; Saxena, R; Mohan, J; Singh, RP
Contents In the present study, the expression profile of luteinizing hormone receptor (LHR) was investigated in the ovary, magnum and uterus and in hierarchcal follicles (F‐1, F‐2, F‐3 and F‐4) of hens subjected to moulting to establish their involvement in moulting and presence in non‐gonadal tissues. Fifty‐two layers (72 weeks) were subjected to moult for a period of 14 days. Four birds were sacrificed each time on 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12 and 14 days of moulting, and samples (ovary, magnum, uterus and hierarchal follicles) were collected aseptically for the quantitative study by real‐time polymerase chain reaction. The ovary, isthmus, uterus and magnum weight reduced significantly during induced moulting. From the 4 DOM, this reduction was drastic and reached approximately 80% of original weight in the case of ovary, isthmus and magnum and approximately 65% of original weight in the case of uterus on 14 DOM. Ovarian yellow follicles decreased gradually from 1 DOM to 4 DOM, after that no normal yellow follicle was observed in moulted bird. The number of atretic follicles increased gradually during the course of induced moulting, reaching the peak at 5 DOM. The LHR mRNA was detected in non‐gonadal tissues like magnum and uterus. The LHR expression was significantly (p < 0.05) down regulated in ovary, magnum and uterus throughout the treatment. These results indicated that LHR may have a role in reproductive tissue regression during moulting.